Malaysian education blueprint, 2015-2025 (higher education) (Kementerian Pendidikan Malaysia, 2015)
In 2013, the Ministry (of Education) began developing the Malaysian Education Blueprint 2015-2025 (Higher Education) or the MEB (HE). Over the course of two years, the Ministry drew on multiple sources of input, from Malaysian and international education experts, to leaders of Malaysian HLIs and members of the public. The end product is a blueprint that was developed by Malaysians, for Malaysians, and that will equip Malaysia for the final leg of its journey towards becoming a high-income nation.